Building the 8-star doctor: a modified Delphi study to define, teach, and assess health professions education for undergraduate medical students - Sara Jamil Khan; Rahila Yasmeen; Shazia Imran (BMC Medical Education)
Abstract Background As global trends in medical education shift toward integrated curricula, there remains a lack of consensus on the core components of Health Professions Education (HPE) to be embedded within undergraduate medical programs. This study aims to identify and structure key HPE topics relevant to the MBBS curriculum, with the goal of enhancing students’ foundational competencies in teaching, leadership, and professionalism. It also seeks to propose appropriate pedagogical approaches and assessment strategies for effective curricular integration. Methods A multi-phase, mixed-methods study design was employed. The initial phase involved a comprehensive literature review, followed by expert consensus through the Nominal Group Technique (NGT) with 19 national HPE professionals. This was succeeded by a three-round modified e-Delphi process involving 69 HPE experts across Pakistan. Participants rated the importance of proposed content items using a three-point Likert scale. Topics achieving ≥ 80% consensus were retained. The stability of responses across rounds was assessed using McNemar’s test. Teaching methodologies and assessment tools were finalized in the third round. Results The NGT process streamlined 54 initial content items to 37, eliminating 12, modifying 5, and adding 2 new topics. The Delphi process led to consensus on 17 key items, including bedside teaching, procedural skills, leadership, communication, professionalism, medical ethics, and patient safety. Preferred teaching strategies included small-group discussions (SGD) and large-group interactive sessions (LGIS), both receiving over 50% expert agreement. Objective Structured Teaching Exercises (OSTE) emerged as the most endorsed assessment approach. Response rates for the three Delphi rounds were 93%, 96%, and 90%, respectively. Conclusion This study presents a consensus-driven framework for the integration of HPE into undergraduate medical curricula. The findings underscore the relevance of structured teaching, evidence-based learning strategies, and pragmatic assessments. The framework has potential applicability for scalable curricular reforms in five-year undergraduate medical programs globally.